A psychogeographical tracing of place attachment in selected poems of Kuala Lumpur - Mohd Fadhli Shah Khaidzir; Ruzy Suliza Hashim; Noraini Md Yusof (Penerbit Universiti Kebangsaan Malaysia, 2022)
Individuals may imbue a location with profound significance. We pay attention to locations in literature because they are dense with importance. Kuala Lumpur as a location offers insights and several levels of relevance to individuals seeking to understand and examine their surroundings. The establishment of a connection between the person and the region results in authentic and significant experiences and interpretations, which are portrayed in poetry as information and knowledge about the environment for readers to read and be inspired by. The objective of this article is to investigate how different Malaysian poets depict Kuala Lumpur as a place in selected poems from Malchin Testament: Malaysian Poems (2017). While the location remains constant, the findings and knowledge gained via human observation and experience alter, especially over time. This may be seen through the lens of psychogeography, which is concerned with how an individual interacts with and observes a place, as well as how this affects his or her perception of the environment via the use of ideas and behaviour. The chosen poems about Kuala Lumpur were written by a variety of poets throughout the city's evolution from a township to the bustling metropolis it is today. These poems address a variety of features that contribute to the city's development, including people, history, architecture, and other traits that, in the poets' opinion, define the city. The poets' affinities are shown via their attention on important and compelling issues that characterise Kuala Lumpur. Thus, by concentrating our attention on Kuala Lumpur as a city, we may get a deeper understanding of the link between the individual and the environment. This will foster a stronger feeling of connection between the person and the city, an experience that is beyond the human eye's capability to perceive.